‏An Enhanced Approach to Improve the Security and Performance for Deduplication - et al., Nourah Almrezeq (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cloud service providers providing users with efficient and effective storage and transmission of data. To reduce storage costs and save bandwidth, cloud service providers are attracted to use data de-duplication feature. Cloud users are interested in using the cloud safely and privately to protect the data they share on the cloud. Therefore, they encrypt the data before uploading it to the cloud. Since the intent of encryption conflicts with the de-duplication function, the data de-duplication feature becomes a hard problem. Existing de-duplication methods are ineffective in terms of both security and efficiency. They are either vulnerable to brute force attacks that enable the attacker to retrieve files, or they are computationally expensive. That is what drives us to suggest a method for removing duplicate data that is both performance and security effective. We'll start with a description of the implementations and functionality of de-duplication strategies, then move on to the literature that proposes various approaches to de-duplication and the security and efficiency problems that existing approaches face. Via the use of the AES-CBC algorithm and hashing functions, we have proposed an enhancement to improves the performance and protection of data de-duplication for users. Without the involvement of a third party, users' keys are created in a consistent and safe manner. We prove the efficacy of the recommended solution by putting it into practice and comparison with the existing techniques.